2016
DOI: 10.1007/s13721-016-0127-4
|View full text |Cite
|
Sign up to set email alerts
|

Epitope prediction for MSP119 protein in Plasmodium yeolii using computational approaches

Abstract: Malaria disease is caused by the transmission of Plasmodium, through the bite of a female Anopheles mosquito. Although the Plasmodium life-cycle has been extensively characterized, relatively little is known about sporozoite interaction with host organelles and proteins. Individuals that survive continuous exposure to infection do eventually develop clinical immunity, suggesting that a vaccine against asexual blood stage of the parasite is achievable. The merozoite surface protein (MSP1 19 ) of Plasmodium yoel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In this study, bioinformatics tools were used to select linear epitopes for B-cells based on the combination of three prediction algorithms, BepiPred, AAP12, and BCPred12, based on the assumption that the combination of different algorithms has greater accuracy, especially when dealing with protozoa [30]. Our selected peptides show good score values, including algorithms that are considered more restrictive, which is the case for BepiPred [31,32]. Furthermore, using the PPI networks, it was possible to evidence the biological importance of the proteins that contained the selected peptides, as they can participate in the modulation of cellular activities like virulence, metabolism regulation, or latency behavior in some species of the parasite [33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, bioinformatics tools were used to select linear epitopes for B-cells based on the combination of three prediction algorithms, BepiPred, AAP12, and BCPred12, based on the assumption that the combination of different algorithms has greater accuracy, especially when dealing with protozoa [30]. Our selected peptides show good score values, including algorithms that are considered more restrictive, which is the case for BepiPred [31,32]. Furthermore, using the PPI networks, it was possible to evidence the biological importance of the proteins that contained the selected peptides, as they can participate in the modulation of cellular activities like virulence, metabolism regulation, or latency behavior in some species of the parasite [33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the failure of further enhancement of T cell responses by magnetofection in our study may partially be due to the complexity of this MSP1 19 antigen processing and presentation in vivo. Additionally, a recent study using computational approaches to predict epitopes within MSP1 19 found that B cell epitopes have the lowest energy score compared to the T cell epitopes, indicating a strong binding affinity toward the receptor and, therefore, stronger humoral responses overall [ 48 ]. There were six potential B cell epitopes and two potential T cell epitopes predicted as potential candidates for vaccine development against malaria within the MSP1 19 antigen [ 48 ], suggesting a strong humoral-mediated immune response by this antigen.…”
Section: Discussionmentioning
confidence: 99%
“…Ramachandran plot showed the distribution of ϕ, ψ angles with 89.0% residues in the most favorable core region, 6.4% residues in additional allowed region, and 2.5% residues in the generously allowed region. On the basis of this validation, we concluded in silico generated ATP7B model as accurate . All these 13 nsSNPs were subjected to Accelrys Discovery Studio 2, Build Mutant protocol, to generate a model for each functional nsSNP.…”
Section: Methodsmentioning
confidence: 99%
“…On the basis of this validation, we concluded in silico generated ATP7B model as accurate. 42 All these 13 nsSNPs were subjected to Accelrys Discovery Studio 2, Build Mutant protocol, to generate a model for each functional nsSNP. Energy minimizations for all structures were accomplished using the Accelrys Discovery Studio 2, Minimization protocol.…”
Section: Sequence-based Snp Effect Analysis Functional Disease-relatementioning
confidence: 99%